Risk factors for pulmonary complications following laparoscopic gastrectomy: A single-center study. Issue 32 (August 2016) - Ntutumu, Redondo; Liu, Hao; Zhen, Li; Hu, Yan-Feng; Mou, Ting-Yu; Lin, Tian; I, Balde A.; Yu, Jiang; Li, Guo-Xin
Abstract : Abstract: The risk factors associated with postoperative pulmonary complications (PPCs) following laparoscopic gastrectomy have not been well studied. We sought to identify the risk factors for PPCs following gastric cancer surgery. A retrospective analysis was performed on all gastric cancer patients in a prospective database who underwent a laparoscopic gastrectomy from 2004 to 2014. The potential risk factors for PPCs were evaluated. PPCs occurred in 6.8% (83/1205) of patients and included pneumonia in 56 (67.5%) patients, pleural effusion in 26 (31.3%) patients, and pulmonary embolism in 1 (1.2%) patient. The multivariate analysis identified the following significant risk factors for PPCs: advanced age (odds ratio [OR] = 1.043, 95% confidence interval [CI] = 1.021%, 1.066%), chronic obstructive pulmonary disease (COPD) (OR = 17.788, 95% CI = 2.618%, 120.838%), total gastrectomy (OR = 2.781, 95% CI = 1.726%, 4.480%), time to first diet (OR = 1.175, 95% CI = 1.060%, 1.302%), and postoperative hospital stay (OR = 1.015, 95% CI = 1.002%, 1.028%). The risk factors for pneumonia included advanced age (OR = 1.036, 95% CI = 1.010%, 1.063%), total gastrectomy (OR = 3.420, 95% CI = 1.960%, 5.969%), and time to first diet (OR = 1.207, 95% CI = 1.703%, 1.358%). Only pancreatectomy was a risk factor for pleural effusion (OR = 9.082, 95% CI = 2.412%, 34.206%). The frequency of PPCs in patients with gastric cancer who underwent laparoscopic surgery was relatively high. Patients with cardiac and pulmonary comorbidities and those who undergo total gastrectomy and combined resection should be considered at high risk.